"Algorithms on Strings, Trees, and Sequences: Computer Science and Computational Biology" - Gusfield (Dan) (2005)
algorithms ; Computer Science ; Computational Biology
41565a.jpg;41565b.jpg;41565c.jpg;41565d.jpg;41565e.jpg
22.5
Keywords: algorithms ; Computer Science ; Computational Biology